2022
DOI: 10.3389/fpls.2022.1013304
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of nitrogen starvation-induced leaf senescence

Abstract: Nitrogen (N), a macronutrient, is often a limiting factor in plant growth, development, and productivity. To adapt to N-deficient environments, plants have developed elaborate N starvation responses. Under N-deficient conditions, older leaves exhibit yellowing, owing to the degradation of proteins and chlorophyll pigments in chloroplasts and subsequent N remobilization from older leaves to younger leaves and developing organs to sustain plant growth and productivity. In recent years, numerous studies have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 157 publications
0
7
0
Order By: Relevance
“…Leaf senescence is the final stage of leaf development, in which organelles and macromolecules are actively degraded to relocate nutrients into newly developing leaves, or storage organs (seeds) (Domínguez & Cejudo, 2021; Kim, Woo, & Nam, 2016; Sakuraba, 2022; Woo et al., 2019; Zhang, Guo, et al., 2021). The initiation of leaf senescence is controlled by endogenous factors including senescence‐promoting and ‐suppressing phytohormones, metabolites, and the status of photosynthesis (Huang et al., 2022; Kusaba et al., 2013; Liebsch & Keech, 2016; Sakuraba et al., 2012; Woo et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf senescence is the final stage of leaf development, in which organelles and macromolecules are actively degraded to relocate nutrients into newly developing leaves, or storage organs (seeds) (Domínguez & Cejudo, 2021; Kim, Woo, & Nam, 2016; Sakuraba, 2022; Woo et al., 2019; Zhang, Guo, et al., 2021). The initiation of leaf senescence is controlled by endogenous factors including senescence‐promoting and ‐suppressing phytohormones, metabolites, and the status of photosynthesis (Huang et al., 2022; Kusaba et al., 2013; Liebsch & Keech, 2016; Sakuraba et al., 2012; Woo et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…During leaf senescence, N derived from the degradation of macromolecules (e.g., proteins, DNA, RNA) is relocated to young, emerging leaves, developing flowers, and seeds, mainly in the form of nitrate or N‐rich amino acids (Distelfeld et al., 2014; Hörtensteiner & Feller, 2002). Leaf senescence is promoted by a shortage of N supply, probably for infallibly reallocating N to young tissues (Agüera et al., 2010; Estiarte et al., 2022; Sakuraba, 2022; Yang & Udvardi, 2018). It is also interesting that Arabidopsis thaliana knockout mutants lacking nitrate transporter NRT1.5 show an early establishment of senescence during nitrate starvation‐induced senescence, due to altered foliar potassium levels (Meng et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The constraints observed in the non-inoculated plants' ETC may be partially a result of RuBisCo heat-induced inhibition, as described in the studies of [69,70]. Additionally, N-deficiency lowers the PS II protein repair rate and can be related to the degradation of the photodamaged D1 protein, impairing the photochemical apparatus [71,72]. PGPR inoculation had a mitigating heat stress effect, allowing for the accumulation, synthesis and remobilization of nitrogenous-related compounds in grapevine leaves, such as proline, which was found to present control values in inoculated plants exposed to HW treatment.…”
Section: Discussionmentioning
confidence: 97%
“…These CsSGR HapG allele‐containing accessions were therefore valuable for cucumber breeding and were selected over time. The interaction between SGR and other CCEs, including NON‐YELLOW COLORING 1 (NYC1), and with LHCII for Chl detoxification have been demonstrated (Sakuraba et al, 2012, 2013; Sakuraba, 2022). Our LCI assay showed that the interaction between CsSGR HapG and CsNYC1 was reduced, indicating that the natural variant of CsSGR enhanced LT tolerance by affecting its interaction with CsNYC1, and consequently reducing its ability to degrade Chl.…”
Section: Discussionmentioning
confidence: 99%